The Composition and Predictive Function of the Fecal Microbiota Differ Between Young and Adult Donkeys - Xing, Jingya; Liu, Guiqin; Zhang, Xinzhuang; Bai, Dongyi; Yu, Jie; Li, Lanjie; Wang, Xisheng; Su, Shaofeng; Zhao, Yiping; Bou, Gerelchimeg; Dugarjaviin, Manglai (Frontiers in Microbiology, 2020)
The diverse community of microorganisms inhabiting the gastrointestinal tract of monogastric herbivores play critical roles in the absorption of nutrients and keep the health for the host. However, its establishment at different age groups has not been quantitatively and functionally examined. And the knowledge of microbial colonization and its function of intestine tract during different age donkeys are still limited. Through applying the V3–V4 region of the bacterial 16S rRNA gene and functional prediction on fecal samples from different age donkeys, we characterized the gut microbiota during the different age groups. In contrast to the adult donkeys, the gut microbiota of the young donkeys showed significant less resemblance to them. The microbial data showed that diversity and richness were increased with age, but a highly individual variation of microbial composition was observed at month 1. Principal coordinate analysis (PCoA) revealed significant difference across five time points in the faeces. The abundance of Bacteroides, Lactobacillus and Odoribacter tended to decrease, while the proportion of Streptococcus was significantly increased with age. For functional prediction, the relative abundance of pathways had significant difference across different age groups in faeces (P<0.05 or P<0.01). The analysis of beta diversity and microbial functions clearly divided the donkeys into foals (≤3 months old) and adults (≥7 months old). Microbial community composition and structure had distinctive features at each age group, in accordance with functional maturation of the microbiota. Our findings established a framework for understanding the composition and function of the fecal microbiota to differ between young and adult donkeys.